Luminosity determination in pp collisions at [Formula: see text] = 8 TeV using the ATLAS detector at the LHC - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2016)
The luminosity determination for the ATLAS detector at the LHC during pp collisions at [Formula: see text] 8 TeV in 2012 is presented. The evaluation of the luminosity scale is performed using several luminometers, and comparisons between these luminosity detectors are made to assess the accuracy, consistency and long-term stability of the results. A luminosity uncertainty of [Formula: see text] is obtained for the [Formula: see text] of pp collision data delivered to ATLAS at [Formula: see text] 8 TeV in 2012.